All Consuming Images: The Politics Of Style In Contemporary Culture - Stuart Ewen (USA Basic Books, 1988)
A provocative, compelling, and entertaining look at how the power of images dominates every aspect of our lives.
Keywords: Art; Design; History; Nonfiction; Sociology; Psychology; (THD-203) Design Theory 2